IMPLEMENTASI MODEL PBL DALAM PEMEBLAJARAN IPAS PADA PESERTA DIDIK KELAS V SDN TEGALGANDU 02 - Edi Susanto; Laelia Nurpratiwiningsih; Dedi Romli Triputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the Problem Based Learning (PBL) model in Ilmu Pengetahuan Alam dan Sosial (IPAS) instruction for fifth-grade students at SDN Tegalgandu 02. Prior studies on PBL in elementary IPAS classrooms have largely relied on quantitative designs measuring learning outcomes, critical thinking, or student engagement, leaving a gap in qualitative accounts of how the model unfolds in daily classroom practice. This research used a qualitative case study approach involving a fifth-grade teacher and ten students selected through purposive sampling based on their level of learning activeness. Data were collected through classroom observation of instruction on the water-cycle topic, in-depth interviews, and documentation, then analyzed following the interactive model of data condensation, data display, and conclusion drawing, with credibility established through source and technique triangulation. The findings show that the teacher carried out all five PBL syntax stages, problem orientation, organizing students, guiding investigation, developing and presenting work, and analyzing and evaluating the problem-solving process, producing instruction that was active, student-centered, contextual, and collaborative. Implementation still faced constraints: limited instructional time, uneven student ability and engagement, and some students' reluctance to voice their opinions. The teacher addressed these constraints through more intensive scaffolding, heterogeneous grouping, motivational reinforcement, and more deliberate time management, allowing the intended learning objectives to be achieved.